Digital transformation and its role in progressing the relationship between states and their citizens - Edwards, Sam B. III 1969; Santos, Diogo 1978 (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2020)
"This book examines the relationship between governments and their constituents, and how this relationship is impacted by emerging technologies"--Provided by publisher c Provided by publisher